If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a = (5x + -3)(x + 2) Reorder the terms: a = (-3 + 5x)(x + 2) Reorder the terms: a = (-3 + 5x)(2 + x) Multiply (-3 + 5x) * (2 + x) a = (-3(2 + x) + 5x * (2 + x)) a = ((2 * -3 + x * -3) + 5x * (2 + x)) a = ((-6 + -3x) + 5x * (2 + x)) a = (-6 + -3x + (2 * 5x + x * 5x)) a = (-6 + -3x + (10x + 5x2)) Combine like terms: -3x + 10x = 7x a = (-6 + 7x + 5x2) Solving a = -6 + 7x + 5x2 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Simplifying a = -6 + 7x + 5x2
| 3x^2+2x=2x+27 | | 4a-3=2a+9 | | 2x^2+3-3=0 | | 8+3x=-3x-4 | | 15x-5+13x+13=180 | | 2(y-7)=5y-32 | | 2(5t-2)=20-(2t) | | 3xwhat=54 | | -2u+12=2(u+4) | | 12t=30 | | 15x-5+14x+4=180 | | -7+x=-5x+29 | | 6(v-6)=9v-33 | | 3d+14=19 | | (4x-15)+5x=30 | | 13x+169=0 | | u=3(7n+34)+7(n+1) | | 1X+4=4X-10 | | 5[20+p]=2[30+p] | | 4x+5=27-7x | | 8x-3=4y+16 | | 32-(3x-2(2x-3))=183 | | 40-4(x-3)=7x-5 | | 4(f-5)=-24 | | 2cos^2x=coax | | 32x^2+48x^4=0 | | 8.56x+51.36=102.72 | | -26.7+3.4r=4.4(r-6) | | D(20)=22g | | -10(s+2)=53 | | 6a+11=28+83 | | 9999999999999-24533357= |